Ductility factor of RC building frames with different infill wall configurations under low intensity far field earthquake effects - Adnan, Azlan (2012)
It is not a well accepted practice for engineers to incorporate seismic resistance into structural design in regions of low earthquake intensity such as Malaysia. Introducing ductility design criteria into structural plan is less favoured by the nation’s industry. The increment in construction cost is another main reason behind this impediment. Therefore, it is rather important to understand the behaviour and capacity of non-earthquake designed structure under local earthquake condition, despite being minor. This paper investigates the ductility performance of non-ductile reinforced concrete frames with different precast infill locations. Using localized soil response spectrums, pushover analysis for the frame-infill system is performed at both serviceability limit state (SLS) and ultimate limit state (ULS) of vertical loading, respectively. The behaviour factor (q0) and displacement behaviour factor (qA) are presented, and implication of using these factors in judging the suitability of DCL structure in resisting low to moderate seismic demand is included.